2018
DOI: 10.1007/978-3-319-93818-9_42
|View full text |Cite
|
Sign up to set email alerts
|

Using Discrete-Event-Simulation for Improving Operational Efficiency in Laboratories: A Case Study in Pharmaceutical Industry

Abstract: Just-in-time delivery has become a key aspect of pharmaceutical industry when loyalizing customers and competing internationally. Additionally, prolonged lead times may lead to increased work-inprocess inventory, penalties for non-compliance and cost overrun. The problem is more complex upon considering a wide variety of products as often noted in pharmaceutical companies. It is then relevant to design strategies focusing on improving the delivery performance. Therefore, this paper proposes the use of Discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…The only exception was evidenced in High LWBS where LM was found as the most preferred approach. Authors have mostly employed this approach since: i) it provides a reliable representation of the patient journey within EDs so that factors and interactions affecting emergency care can be easily identified, ii) it records individual entity experience which is desirable for analyzing inefficiency patterns, iii) it facilitates engagement with decision-makers through animation, and iv) it allows ED managers to pretest potential improvement scenarios [226][227][228][229]. It is also noteworthy that researchers have decided to utilize lean manufacturing preferentially since it i) allows ED managers identifying and removing the causes of emergency care variability, thus minimizing prolonged stays within these departments, ii) enables managers to detect and reduce wastes of resources (including time and cost overruns), iii) increases patient satisfaction rates, and iv) promotes collaborative work and increases the competences of medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was evidenced in High LWBS where LM was found as the most preferred approach. Authors have mostly employed this approach since: i) it provides a reliable representation of the patient journey within EDs so that factors and interactions affecting emergency care can be easily identified, ii) it records individual entity experience which is desirable for analyzing inefficiency patterns, iii) it facilitates engagement with decision-makers through animation, and iv) it allows ED managers to pretest potential improvement scenarios [226][227][228][229]. It is also noteworthy that researchers have decided to utilize lean manufacturing preferentially since it i) allows ED managers identifying and removing the causes of emergency care variability, thus minimizing prolonged stays within these departments, ii) enables managers to detect and reduce wastes of resources (including time and cost overruns), iii) increases patient satisfaction rates, and iv) promotes collaborative work and increases the competences of medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…[6]. Por otro lado, [7] utilizaron la Simulación de Eventos discretos para mejorar los tiempos de respuesta de un laboratorio de control de la calidad en el sector farmacéutico. También (Restrepo Tamayo, L.M.)…”
Section: Estudios Primarios De La Literaturaunclassified
“…Because in the literature reviewed in Science Direct, Scopus and Isi, no study of this type was found, this research will serve to provide an improvement in the wood sector, As the improvement obtained in the pharmaceutical sector by [25] where they used the simulation of discrete events for operational improvement in an analysis laboratory.…”
Section: Literature Reviewmentioning
confidence: 99%